1987
DOI: 10.1002/bit.260290907
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic interesterification of fats: Laboratory and pilot‐scale studies with immobilized lipase from Rhizopus arrhizus

Abstract: An immobilized lipase suitable for fat interesterification has been prepared by precipitation with acetone of a commercial lipase from Rhizopus arrhizus onto diatomaceous earth. As observed previously with a less active enzyme from Aspergillus sp., the interesterification activity was enhanced by addition of purified lipase or by high loadings of commercial enzyme. The interesterification activities reached maximum values in both cases. For immobilized preparations with purified enzyme, interesterification act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 5 publications
2
28
0
Order By: Relevance
“…Other minor components related to oil quality are also very important for the lipase activity. It was observed that a high purity of feedstock had better performance to maintain the enzyme activity by using high purity of shea oleine instead of shea oil [26]. The oil with high peroxide value (PV) decreased initial reac- tion rate for the glycerolysis [27].…”
Section: Feedstock Qualitymentioning
confidence: 99%
“…Other minor components related to oil quality are also very important for the lipase activity. It was observed that a high purity of feedstock had better performance to maintain the enzyme activity by using high purity of shea oleine instead of shea oil [26]. The oil with high peroxide value (PV) decreased initial reac- tion rate for the glycerolysis [27].…”
Section: Feedstock Qualitymentioning
confidence: 99%
“…This type is versatile and simple and provides more surface area for reaction than membrane reactors. The packed-bed reactor has been employed for lipase-catalyzed hydrolysis and interesterification reactions by a number of investigators (Layvayre and Baratti, 1982;Macrae, 1983;Wisdom et al, 1987;.…”
Section: Packe'd-bed or Fixed-bed Reactormentioning
confidence: 99%
“…Granules of various sizes with lipase attached to them (Layvayre and Baratti, 1982;Macrae, 1983;Wisdom et al, 1987; or lipase-containing dried mycelia (Bell et al, 1981) are usually confined in a jacketed column.…”
Section: Packe'd-bed or Fixed-bed Reactormentioning
confidence: 99%
See 1 more Smart Citation
“…Interesterification is a process that is used to modify the structure and composition of oils and fats to improve their physical and nutritional properties (1,2). Conventionally, the interesterification reaction is promoted by sodium metal or sodium alkoxide to catalyze acyl migration between triglyceride molecules and to produce randomly distributed fatty acyl residues among the triglyceride molecules (3).…”
Section: Introductionmentioning
confidence: 99%